2017
DOI: 10.2147/ijnrd.s131220
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic denervation increases renal blood volume per cardiac cycle: a serial magnetic resonance imaging study in resistant hypertension

Abstract: Aim: Preclinical studies have demonstrated improvements in renal blood flow after renal sympathetic denervation (RSDN); however, such effects are yet to be confirmed in patients with resistant hypertension. Herein, we assessed the effects of RSDN on renal artery blood flow and diameter at multiple time points post-RSDN. Methods and results: Patients (n=11) with systolic blood pressures ≥160 mmHg despite taking three or more antihypertensive medications at maximum tolerated dose were recruited into this single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Recently, Ott and colleagues conducted an observational pilot study of 27 patients with CKD stages 3 and 4 and reported that the RSD treatment of hypertension decreased BP and augmented eGFR by +1.5±10 mL/min/1.73 m 2 , halting the decline in renal function. Consistent with our findings, unpublished data from the Adelaide and Renal EnligHTN Blood Flow study, which was presented at the American Heart Association Scientific Sessions 2014, showed increased eGFR and a reduction in the levels of urinary protein excretion and plasma aldosterone in refractory hypertension patients with eGFR ≥45 mL/min/1.73 m 2 6 months after renal denervation …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Ott and colleagues conducted an observational pilot study of 27 patients with CKD stages 3 and 4 and reported that the RSD treatment of hypertension decreased BP and augmented eGFR by +1.5±10 mL/min/1.73 m 2 , halting the decline in renal function. Consistent with our findings, unpublished data from the Adelaide and Renal EnligHTN Blood Flow study, which was presented at the American Heart Association Scientific Sessions 2014, showed increased eGFR and a reduction in the levels of urinary protein excretion and plasma aldosterone in refractory hypertension patients with eGFR ≥45 mL/min/1.73 m 2 6 months after renal denervation …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, unpublished data from the Adelaide and Renal EnligHTN Blood Flow study, which was presented at the American Heart Association Scientific Sessions 2014, showed increased eGFR and a reduction in the levels of urinary protein excretion and plasma aldosterone in refractory hypertension patients with eGFR ≥45 mL/min/1.73 m 2 6 months after renal denervation. 16 Increased sympathetic tone, a well-known risk factor for CVD, is also frequently present in patients with essential hypertension and in those with CKD. [37][38][39] In both hypertension and renal failure, the mechanisms of the hyperadrenergic state are manifold and include reflex and neurohumoral pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While RDN has been used predominantly to treat resistant hypertensive patients ( Figure 5; Symplicity et al, 2010;Krum et al, 2014), it is likely of beneficial value in CKD. Indeed, RDN has demonstrated GFR improvement (Kiuchi et al, 2013(Kiuchi et al, , 2014Delacroix et al, 2014) and reduction of albuminuria (Kiuchi et al, 2013(Kiuchi et al, , 2014Ott et al, 2014;Schmieder et al, 2014), although these studies are limited by a short follow up period. Kiuchi et al (2016a) reported cardiac structural and functional enhancement, which were associated with eGFR improvement in a resistant hypertensive cohort with CKD at follow-up 6 month FIGURE 6 | Sympathetic and parasympathetic nervous system cardiac arrhythmogenic effects.…”
Section: Renal Denervationmentioning
confidence: 99%